An Imminent Approach on Stimulus towards Customer Perceptiveness at Service Sector in South India - Kumar, T. Rekha Kiran (International Journal of Psychosocial Rehabilitation, 2020)
Indeed, the alleged that high superficial quality service leads to post purchases, but attaining that repeated purchase level, may be a substratum for any business. Thus a better considerable relationship between tangible product, service quality, service methodology, service render involvement and service delivery from service sector domain and purchase intentions, purchase decision and consumer satisfaction from a consumer end, may generate a roadmap to develop a model the consumer service provider relationship process on intangible services. It may also provide service practitioners with alarm to donate marketing attention on service gap and scarce corporate resources. This study intends to contribute to the enlargement of a theoretical framework that may integrate perceived product, service quality, and service methodology in delivering the service. Based on the reviews the literature, appropriate research measures were identified. Implications on service sector development were analyzed and discussed, limitations of the study were noted and possible areas for further research were indicated.